Prevalence of Major Depressive Disorder among Mothers of Children and Adolescents with Attention Deficit Hyperactivity Disorder Attending a Tertiary Care Centre - Dr Sarika P; Gopalan, Dr Mohan Roy G (International Journal of Medical Research and Review, 2023)
Abstract Introduction : Attention deficit hyperactivity disorder (ADHD) accounts for the majority of referrals to child and adolescent psychiatry services because of the associated poor scholastic performance. Despite the possibility of depressive symptoms in caregivers, there is a paucity of studies on major depressive disorder among mothers of children and adolescents with ADHD in our setting Objectives : Assessing the prevalence of major depressive disorder and the association of sociodemographic and clinical variables among mothers of children & adolescents with ADHD attending a tertiary care centre. Studying the correlation between the severity of ADHD and maternal depression. Methods: Cross-sectional study on 150 mothers of children and adolescents aged 5-18 years with ADHD attending the Child and Adolescent Psychiatry Clinic of the Govt. Medical College, Thiruvananthapuram. Results : The prevalence of Major Depressive Disorder among mothers belonging to the age group of 30‒39 years was found to be 20%. Across age groups, 28.7% of the subjects had minimal depressive symptoms, while 10% each had mild and moderate symptoms. We found a positive correlation between the severity of maternal depression and the child’s ADHD. The association of major depressive disorder with medical comorbidities and having another offspring with ADHD was statistically significant. Conclusion: Owing to the statistically high prevalence of depressive disorders, routine screening for the depressive symptoms has to be considered for mothers when the children are diagnosed with ADHD, with the provision for appropriate intervention. Keywords: Attention Deficit Hyperactivity Disorder; Major Depressive Disorder, Scholastic performance, Sociodemographic and clinical variables,